The Effect of Profitability, Liquidity, Firm Size, Net Working Capital, Leverage, and Growth Opportunity on Cash Holding: Empirical Study From Property and Real Estate Companies Listed in Indonesian Syariah Stock Index (ISSI) for The Period 2019-2023 - Mariska, Uut; Suhendar, S.; Nurmalia, Gustika (Golden Ratio of Finance Management, 2025)
Cash is the company's most liquid asset and is crucial for financing its operational activities. Therefore, effective cash management is essential to ensure business continuity. This study aims to provide empirical evidence on the influence of profitability, liquidity, firm size, net working capital, leverage, and growth opportunities on cash holdings in property and real estate companies listed on the Indonesian Sharia Stock Index (ISSI) for the period of 2019–2023. Using a purposive sampling method, the study selected 23 samples from 82 property and real estate companies registered with the ISSI during the period. The data were collected and processed using Microsoft Excel 2019 and EViews 12. The findings indicate that profitability, liquidity, firm size, net working capital, and growth opportunities positively and significantly affect cash holdings, while leverage has no effect. This research makes a unique contribution by focusing on property and real estate companies within Indonesia's Islamic capital market, an area rarely studied in prior research. Additionally, it enriches the literature on factors influencing cash holdings by considering companies that operate based on Sharia principles. The results are expected to provide valuable insights for company management in optimizing cash management and serve as a reference for investors making decisions regarding sharia-compliant companies.